PENGARUH JARAK TANAMAN KAPAS (Gossypium hirsutum) DAN PEMAKAIAN JENIS PUPUK TERHADAP PERTUMBUHAN DAN PRODUKSI KAPAS BERBIJI POLA TUMPANGSARI KEDELAI (Glycium max) - Amiroh, Ana (saintis, 2009)
This experiment was carried out to determine whether the spacing of cotton and the use of fertilizers KC1, Fosfo N and M-Dext has an influence on plant growth and production of cotton in rainfed cropping pattern of soybean grown after rice crop was harvested. The hypothesis of this trial, allegedly with the use of liquid manure as fertilizer N Fosfo of over 2 liters / ha in cotton plants will have increased growth and yield of cotton in the use of l00 x 40cm spacing. From the results of this experiment showed that the treatment plant spacing generally do not indicate a direct influence on the growth of cotton plants. Production phase spacing of 150 x 40 cm showed better results than the spacing of 40 cm and 100 x 125 x 40 cm on the parameters of the number of flower buds and fruit number of cotton. For treatment fosfo N fertilizer usage from the results of this experiment showed the effect of increased growth and yield of cotton.